A watch-and-wait approach for locally advanced rectal cancer after a clinical complete response following neoadjuvant chemoradiation: a systematic review and meta-analysis. (July 2017) - Dossa, Fahima; Chesney, Tyler R; Acuna, Sergio A; Baxter, Nancy N
Summary: Background: A watch-and-wait approach for patients with clinical complete response to neoadjuvant chemoradiation could avoid the morbidity of conventional surgery for rectal cancer. However, the safety of this approach is unclear. We synthesised the evidence for watch-and-wait as a treatment for rectal cancer. Methods: We systematically searched MEDLINE, Embase, and the grey literature (up to June 28, 2016) for studies of patients with rectal adenocarcinoma managed by watch-and-wait after complete clinical response to neoadjuvant chemoradiation. We determined the proportion of 2-year local regrowth after watch-and-wait. We assessed non-regrowth recurrence, cancer-specific mortality, disease-free survival, and overall survival from studies comparing patients who had watch-and-wait versus those who had radical surgery after detection of clinical complete response or versus patients with pathological complete response. Findings: We identified 23 studies including 867 patients with median follow-up of 12–68 months. Pooled 2-year local regrowth was 15·7% (95% CI 11·8–20·1); 95·4% (95% CI 89·6–99·3) of patients with regrowth had salvage therapies. There was no significant difference between patients managed with watch-and-wait after a clinical complete response and patients with pathological complete response identified at resection with respect to non-regrowth recurrence (risk ratio [RR] 1·46, 95% CI 0·70–3·05) or cancer-specific mortality (RR 0·87, 95% CI 0·38–1·99). Although there was no significant difference in overall survival between groups (hazard ratio [HR] 0·73, 95% CI 0·35–1·51), disease-free survival was better in the surgery group (HR 0·47, 95% CI 0·28–0·78). We found no significant difference between patients managed with watch-and-wait and patients with clinical complete response treated with surgery in terms of non-regrowth recurrence (RR 0·58, 95% CI 0·18–1·90), cancer-specific mortality (RR 0·58, 95% CI 0·06–5·84), disease-free survival (HR 0·56, 95% CI 0·20–1·60), or overall survival (HR 3·91, 95% CI 0·57–26·72). Interpretation: Most patients treated by watch-and-wait avoid radical surgery and of those who have regrowth almost all have salvage therapy. Although we detected no significant differences in non-regrowth cancer recurrence or overall survival in patients treated with watch-and-wait versus surgery, few patients have been studied and more prospective studies are needed to confirm long-term safety. Funding: None.